2019
DOI: 10.7554/elife.40760
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair-signature mutations activate gene enhancers across human colorectal cancer epigenomes

Abstract: Commonly-mutated genes have been found for many cancers, but less is known about mutations in cis-regulatory elements. We leverage gains in tumor-specific enhancer activity, coupled with allele-biased mutation detection from H3K27ac ChIP-seq data, to pinpoint potential enhancer-activating mutations in colorectal cancer (CRC). Analysis of a genetically-diverse cohort of CRC specimens revealed that microsatellite instable (MSI) samples have a high indel rate within active enhancers. Enhancers with indels show ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…The observed negative correlation between GC content and mutation rate was consistent with other observations of lower mutation rate in GC rich regions 23,[39][40][41][42] and mechanistically with both GC biased gene conversion 43 and lower rates of cytosine deamination in GC rich regions 10,[44][45][46][47] . Furthermore, the histone modifications H3K4me1 and H3K27ac are known to be associated with lower mutation rates, particularly in active genes 21,[48][49][50] , and several studies have revealed explicit connections between H3K36me3 and DNA mismatch repair 13,16,17 . These chromatin marks were enriched in gene bodies (Fig.…”
Section: Classical Evolutionary Theory Maintains That Mutation Rate Vmentioning
confidence: 99%
“…The observed negative correlation between GC content and mutation rate was consistent with other observations of lower mutation rate in GC rich regions 23,[39][40][41][42] and mechanistically with both GC biased gene conversion 43 and lower rates of cytosine deamination in GC rich regions 10,[44][45][46][47] . Furthermore, the histone modifications H3K4me1 and H3K27ac are known to be associated with lower mutation rates, particularly in active genes 21,[48][49][50] , and several studies have revealed explicit connections between H3K36me3 and DNA mismatch repair 13,16,17 . These chromatin marks were enriched in gene bodies (Fig.…”
Section: Classical Evolutionary Theory Maintains That Mutation Rate Vmentioning
confidence: 99%
“…To this end, utilization of the WGS technology and integration of mutational data with transcriptomic and epigenomic maps have been a proven path to not only identify noncoding mutations but also attribute them with potential biological functions. Various studies have determined functional noncoding mutations with low frequency by integrating mutations with transcriptomes and epigenomes (15,28,32,40). These successes encourage comprehensive characterization of tumors using a compendium of high-throughput assays.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Notably, the highly mutated ER-binding sites are associated with more frequent chromatin loop contacts (ChIA-PET and Hi-C data), and the associated distal genes are expressed at a higher level. Recently, Hung and colleagues (40) revealed that indels with the mismatch repair (MMR) signature led to allelebiased enhancer activation and selection of enhancers in microsatellite instable colorectal cancer. These studies highlight that noncoding mutations induced by a certain mutational process may function collectively.…”
Section: Understanding Functional Roles Of Noncoding Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature on alterations of enhancer elements in CRC is scarce, with only a handful of studies(11-13) with small sample sizes that profiled primary tumors. Furthermore, a comprehensive understanding of other chromatin state alterations and their functional contribution to tumor progression is mostly lacking.…”
Section: Introductionmentioning
confidence: 99%